A Cross-Sectional Study on the Use of Analgesic Medications among Pregnant Women Attending Primary Health Care Centers in Basra City – Iraq - Jasim, Utoor Talib; Fatma Ali; Amira Nasser (Universitas Muhammadiyah Sidoarjo, 2025)
Analgesics are widely used to relieve pain during pregnancy; however, their safety remains a concern due to potential maternal and fetal risks. In Basra, Iraq, pregnant women frequently use analgesics such as paracetamol and NSAIDs, yet limited data exist regarding their prevalence, types, and associated factors in this population. Despite global studies on medication safety, there is insufficient evidence on the patterns of analgesic use among Iraqi pregnant women and their knowledge regarding associated risks. This study aimed to determine the prevalence, types, and influencing factors of analgesic use among pregnant women attending Maternal and Child Health units, and to assess the association between analgesic use and demographic characteristics. A cross-sectional study of 200 pregnant women revealed that 60% reported using analgesics during pregnancy. Paracetamol was the most frequently used (46%), primarily for symptoms of the common cold (27%). While 41% of women believed analgesics were safe, 32% perceived potential risks, and 23% demonstrated limited awareness. The majority obtained information from drug leaflets (45%). No significant associations were found between analgesic use and demographic variables (p > 0.05). This study provides the first structured evaluation of analgesic use among pregnant women in Basra, highlighting gaps in knowledge and perceptions of drug safety. The findings underscore the need for targeted educational programs and strengthened counseling by healthcare providers to promote safe and rational analgesic use during pregnancy. Highlights: 60% of pregnant women reported using analgesics during pregnancy. Paracetamol was the most frequently used analgesic, mainly for common cold symptoms. Knowledge about safe use of analgesics during pregnancy was generally poor, with drug leaflets being the main information source.